2013
DOI: 10.2172/1096255
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental study of CO2-H2O-mineral interactions for carbon sequestration, with emphasis on the nature of the supercritical fluid-mineral interface.

Abstract: In the supercritical CO 2 -water-mineral systems relevant to subsurface CO 2 sequestration, interfacial processes at the supercritical fluid-mineral interface will strongly affect core-and reservoir-scale hydrologic properties. Experimental and theoretical studies have shown that water films will form on mineral surfaces in supercritical CO 2 , but will be thinner than those that form in vadose zone environments at any given matric potential. The theoretical model presented here allows assessment of water satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 111 publications
1
2
0
Order By: Relevance
“…An investigation by Shao et al [40] focused on phlogopite and showed no carbonation following treatment with water-saturated scCO 2 at 103 bar and 95 • C for 159 h. Dissolution pits, and secondary precipitation of silica and kaolinite were observed, however. These results were in agreement with an experiment on muscovite conducted by Bryan et al [41], who observed the same dissolution pits and secondary precipitation after a 14 day treatment in water-saturated scCO 2 at 50 • C and 138 bar. Again, carbonation was not observed.…”
Section: Micasupporting
confidence: 93%
See 1 more Smart Citation
“…An investigation by Shao et al [40] focused on phlogopite and showed no carbonation following treatment with water-saturated scCO 2 at 103 bar and 95 • C for 159 h. Dissolution pits, and secondary precipitation of silica and kaolinite were observed, however. These results were in agreement with an experiment on muscovite conducted by Bryan et al [41], who observed the same dissolution pits and secondary precipitation after a 14 day treatment in water-saturated scCO 2 at 50 • C and 138 bar. Again, carbonation was not observed.…”
Section: Micasupporting
confidence: 93%
“…Wet CO 2 treatment (14 days at 50 • C and 138 bar) experiments on albite conducted by Bryan et al [41] showed dissolution features and the suspected precipitation of silica and phyllosilicates. A similar result was seen by Regnault et al [45] when investigating another plagioclase feldspar, anorthite.…”
Section: Feldsparsmentioning
confidence: 99%
“…This can result in the precipitation of salt crystals in the formation , or in caprock fractures, blocking or reducing flow pathways . Residual water films may form on grain surfaces in the CO 2 -saturated region in water-wet formations . Experimental work has shown that these water films are reactive, resulting in mineral dissolution and precipitation reactions where these reactions may preferentially occur in small pores and pore-throats where water films dominate …”
Section: Storage Securitymentioning
confidence: 99%